2013
DOI: 10.1371/journal.pone.0077101
|View full text |Cite
|
Sign up to set email alerts
|

Recent Patterns in Population-Based HIV Prevalence in Swaziland

Abstract: BackgroundThe 2011 Swaziland HIV Incidence Measurement Survey (SHIMS) was conducted as part of a national study to evaluate the scale up of key HIV prevention programs.MethodsFrom a randomly selected sample of all Swazi households, all women and men aged 18-49 were considered eligible, and all consenting adults were enrolled and received HIV testing and counseling. In this analysis, population-based measures of HIV prevalence were produced and compared against similarly measured HIV prevalence estimates from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
102
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 4 publications
12
102
4
Order By: Relevance
“…HIV is the leading public health concern in Swaziland with HIV prevalence of 32% and annual incidence of 2.4% among 18–49-year-old adults as determined by the 2011 Swaziland HIV Incidence Measurement Survey (SHIMS) [1]. SHIMS also identified substantial differences in prevalence among women (39%) and men (24%) and additionally reported that 38% of HIV-infected individuals were unaware of their HIV status [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV is the leading public health concern in Swaziland with HIV prevalence of 32% and annual incidence of 2.4% among 18–49-year-old adults as determined by the 2011 Swaziland HIV Incidence Measurement Survey (SHIMS) [1]. SHIMS also identified substantial differences in prevalence among women (39%) and men (24%) and additionally reported that 38% of HIV-infected individuals were unaware of their HIV status [1].…”
Section: Introductionmentioning
confidence: 99%
“…SHIMS also identified substantial differences in prevalence among women (39%) and men (24%) and additionally reported that 38% of HIV-infected individuals were unaware of their HIV status [1]. The SHIMS data highlighted the need for an improvement of HIV testing and preventive care services in Swaziland.…”
Section: Introductionmentioning
confidence: 99%
“…Women have less power to negotiate in sexual relationships, and may risk violence from their intimate partners if they assert agency (Brear & Bessarab, 2012). This gendered imbalance in power is implicated in and demonstrated by women's, and particularly young women's, disproportionate risk of HIV infection (Shannon et al, 2012) (e.g., in females aged 18-24 years it is 26%, compared to 5% for males in the same age group (Bicego et al, 2013)). Women, including young women, perform most of the unpaid care-related labour and may be expected to care for their own or other people's children (Nhleko, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…According to the first and only demographic survey conducted, in (CSO & Macro International, 2008), the population prevalence was 19%: that is, one in five people aged two years and more was infected; the adult prevalence (15-49 years) was 26%, and for those considered to be in the sexually and economically active population age group (18-49 years) it was 31% (CSO & Macro International, 2008). This was still the case in 2013 (Bicego et al, 2013). Although data on adolescents are limited due to age-band reporting (0-14 and 15-49), estimates indicate that in 2014 almost 12,000 Swazi adolescents were living with HIV Joint United Nations Programme on HIV and AIDS (2015).…”
mentioning
confidence: 99%
“…Although data on adolescents are limited due to age-band reporting (0-14 and 15-49), estimates indicate that in 2014 almost 12,000 Swazi adolescents were living with HIV Joint United Nations Programme on HIV and AIDS (2015). Furthermore, of the 13,000 people who were newly infected in 2013, 42% were adolescents aged 18-19 years, and this percentage increased to almost 60% when those up to 24 years were counted (Bicego et al, 2013; Ministry of Health [MoH], 2014). The National HTC annual report 2012 further noted that very few adolescents present for testing in the health facilities, despite the successful scale up of HIV testing and counselling (HTC) through decentralisation of services to primary health care facilities and outreach clinics (MoH, 2013).…”
mentioning
confidence: 99%